The Hannover Patient University: Advanced Mini-Med School concept and evaluation results. (February 2017) - Seidel, Gabriele; Kaiser, Birgit; Lander, Jonas; Dierks, Marie-Luise
Objective: To determine whether Hannover Medical School's Patient University, which was developed as the first university-based health education institution in Germany, offers a valuable means of conveying health-related knowledge, competencies and the ability to reflect on health information to its participants. Design: Participatory health education formats included interactive lectures, learning stations and practical training with tutors. Setting: The Patient University was conducted at the facilities of Hannover Medical School, a major German maximum-care hospital and research institution. Methods: To evaluate the programme, data were prospectively collected from participants from 2007 to 2009 using standardised and anonymous questionnaires. One questionnaire included information on sociodemographic data, such as health status, age, gender and post code. A second questionnaire evaluated levels of participant satisfaction, new knowledge and skills gained and understanding of the information provided. Results: Approximately 1, 935 participants enrolled in at least one of 60 events from 2007 to 2009. The response rate from the questionnaire collecting sociodemographic data was 61.4%. A total of 35.2% of participants responded to the event evaluation. After matching both questionnaires, 1, 188 person-specific data sets were available for analysis. Most respondents were women (74.7%), and the median age was 62 years (range: 16–88 years). Satisfaction with the events was rated very positive (average 1.7 on a scale of 1 = excellent to 6 = poor ). Nearly two-thirds of the participants acquired new health-related knowledge and were highly satisfied with the quality of the information received. Participants who self-rated their health status as 'poor' tended to be more critical of what they had received than those in good health. Conclusion: We consider the approach a viable health education advance, and future Mini-Med School programmes may benefit from its methodological and evaluative insights. The development of target group-specific information should be the focus of prospective initiatives and related research.